Religious Freedom & Education: 20th Century’s Trials of Canadian Mennonites - Legault-Laberge, Raphaël Mathieu (Canadian Journal of Education/Revue canadienne de l'éducation, 2019)
This study explores the judicial articulation between religious liberty and education in Canadian Mennonite communities during the 20th century. The purpose of the study is to demonstrate how specific judicial data are linked to general social contexts and to show that some changes in global social contexts and some local elements have an influence on religious liberty in education for a specific religious community. During the 20th century, we can find three trials involving Mennonite education (R. v. Hildebrand ; R. v. Wiebe ; Bal v. Ontario). These judicial data concerning the Mennonites are understood and interpreted in the Canadian social and historical context of the 20th century. Using these rulings as primary literature, the following question is studied: which socio-legal issues linked to religious freedom and education are relevant to these trials? As a result, the study shows that the articulation between religious liberty and education varies for Mennonites according to four considerations: 1) Mennonite faith; 2) relations with other religious groups in which Mennonites had been engaged; 3) factors related to education in itself, interwoven into a plural society and conceived as a public aspect of the identity construction of individuals; and 4) some specific aspects related to the Canadian constitution. Therefore, it is shown that these four socio-judicial considerations, which were associated with the trials involving Mennonites in education, are all concerned, one way or another, with the articulation of religious liberty and education. Keywords: religious freedom, education, Mennonite, Canada, trial